Pengaruh Locus of Control, Komunikasi, dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi pada karyawan KPP Pratama Manado - Purnomo, Kharies D. M. (Universitas Sam Ratulangi, 2018)
The purpose of this study was to determine the effect of locus of control, communication, organizational culture on employee performance with job satisfaction as intervening variable on KPP Pratama Manado employees. The result of research shows that 1) locus of control have positive and significant effect to job satisfaction 2) communication has positive and significant effect to job satisfaction, 3) organizational culture have positive and significant effect to job satisfaction, 4) locus of control has negative and insignificant effect on employee performance, 5) communication has positive and significant effect on employee performance, 6) organizational culture have positive and insignificant effect to employee performance, 7) job satisfaction have positive and significant effect to employee performance.Keywords: Locus of Control, Communication, Organizational Culture, Job Satisfaction, Employee Performance